1983
DOI: 10.1080/14640748308400910
|View full text |Cite
|
Sign up to set email alerts
|

Blocking and Sensory Preconditioning Effects in Morphine Analgesic Tolerance: Support for a Pavlovian Conditioning Model of Drug Tolerance

Abstract: Two experiments on rats tested predictions of a Pavlovian conditioning model of drug tolerance which holds that tolerance is the result of compensatory conditioned responses, developed to environmental stimuli accompanying the drug administrations, which attenuate the direct effects of the drug. In Experiment I, the acquisition of tolerance-modulating properties by the tone component of a tone-light compound stimulus which accompanied morphine administrations was reduced by prior light-morphine pairings (block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…The underlying assumption of many of these theories is that tolerance is the result of an endogenous compensatory system which functions to maintain homeostasis in the presence of drug effects or stimuli associated with the drug. Pavlovian rules of classical conditioning are thought to govern this process, and a plethora of data have been collected which support this idea (e.g., Adams et al 1969;Siegel 1976;Tiffany and Baker 1981;Dafters, et al 1983;Grisel, et al 1994).…”
Section: Introductionmentioning
confidence: 92%
“…The underlying assumption of many of these theories is that tolerance is the result of an endogenous compensatory system which functions to maintain homeostasis in the presence of drug effects or stimuli associated with the drug. Pavlovian rules of classical conditioning are thought to govern this process, and a plethora of data have been collected which support this idea (e.g., Adams et al 1969;Siegel 1976;Tiffany and Baker 1981;Dafters, et al 1983;Grisel, et al 1994).…”
Section: Introductionmentioning
confidence: 92%
“…Further experiments have shown that tolerance to the analgesic effect of morphine is also subject to blocking (Dafters et al, 1983) and overshadowing (Walter & Riccio, 1983), the better known forms of competition between CSs.…”
Section: Audiovisual and Contextual Cues Morphine And Conditionementioning
confidence: 99%
“…Los estímulos condicionados a la droga se ven influidos, por ejemplo, por procedimientos de extinción (Crombag y Shaham, 2002;MacRae y Siegel, 1997), renovación (Betancourt, Corada, et al, 2008), inhibición externa (Siegel, Baptista, Kim, McDonald y Weise-Kelly, 2000;, preexposición al EC (Goodinson y Siegel, 1995), modulación (Betancourt, Inostroza et al, 2008;Ramos et al, 2002), ensombrecimiento (Walter y Riccio, 1983), bloqueo (Dafters, Hetherington, y McCartney, 1983), competencia de claves interoceptivas y exteroceptivas (Betancourt, Díaz y Quezada, 2008), y transferencia Pavlovianas-instrumentales (Quezada, Alarcón, Miguez y Betancourt, 2009), entre otros.…”
Section: Introductionunclassified